Meningkatkan Kemampuan Regulasi Emosi melalui Pendekatan Dialectical Behavior Therapy (DBT) secara Daring - Clarisa Sutjiatmadja; Mita Aswanti Tjakrawiralaksana (Guidena)
Adverse childhood experiences, insecure attachment relationships with parents, the formation of negative self-perceptions, and maladaptive emotional regulation can form strong risk factors for difficulties in emotional regulation and the diagnosis of Major Depressive Disorder (MDD). Several interventions can be used, including the Dialectical Behaviour Therapy (DBT) approach. This study aims to determine the effectiveness of online DBT intervention in adolescents who experience difficulties in emotion regulation and already have a tendency to depressive symptoms. The participant is a teenage girl aged 17 years and 7 months. The research design is a single-case experimental design. The intervention consisted of 1 pre-intervention session, 8 DBT intervention sessions, 1 post-intervention session, and 1 follow-up session. Quantitative analysis was carried out by comparing scores from the Difficulties in Emotion Regulation Scale (DERS), Strength and Difficulties Questionnaire (SDQ), Beck Depression Inventory (BDI), and Subjective Units of Distress (SUD) given before and after the intervention. The results showed that quantitatively there was a decrease in scores of difficulties in emotion regulation, depressive symptoms, and distress faced by the participant compared to before intervention. Qualitatively, emotion regulation skills change in a more positive and adaptive direction.